2016
DOI: 10.1177/0009922816673306
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ Youth’s Perceptions of Primary Care

Abstract: Despite published guidelines on the need to provide comprehensive care to lesbian, gay, bisexual, transgender, and questioning/queer (LGBTQ) youth, there has been limited research related to the deliverance of primary health care to this population. The goals of this study were to learn about LGBTQ youth's experiences with their primary care physicians and to identify areas for improvement. Youth attending 1 of 5 community-based programs completed a written questionnaire and participated in a focus group discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 23 publications
1
54
0
15
Order By: Relevance
“…This research employs the unique approach of having youth comment on themes from healthcare providers, which yields strong recommendations that are directly relevant to the work force and their training needs. In this way, this study builds on previous research from both youth and adults (Corliss et al, 2007;Lerner & Robles, 2017;Roberts & Fantz, 2014;Safer et al, 2016;Snyder et al, 2016;Stoddard et al, 2011) regarding experiences of discrimination and other barriers to healthcare. Intervention and training activities based on these findings will address shortcomings in existing healthcare provider education and the expressed need for more robust training on…”
Section: Theme 2: Training For Healthcare Providersmentioning
confidence: 98%
See 1 more Smart Citation
“…This research employs the unique approach of having youth comment on themes from healthcare providers, which yields strong recommendations that are directly relevant to the work force and their training needs. In this way, this study builds on previous research from both youth and adults (Corliss et al, 2007;Lerner & Robles, 2017;Roberts & Fantz, 2014;Safer et al, 2016;Snyder et al, 2016;Stoddard et al, 2011) regarding experiences of discrimination and other barriers to healthcare. Intervention and training activities based on these findings will address shortcomings in existing healthcare provider education and the expressed need for more robust training on…”
Section: Theme 2: Training For Healthcare Providersmentioning
confidence: 98%
“…Research has identified discrimination and a lack of knowledgeable healthcare providers as major barriers for TGD individuals seeking care (Corliss, Belzer, Forbes, & Wilson, 2007;Lerner & Robles, 2017;Roberts & Fantz, 2014;Safer et al, 2016;Snyder, Burack, & Petrova, 2016;Stoddard, Leibowitz, Ton, & Snowdon, 2011). Ignorance of gender issues may lead to unintentional but nonetheless stigmatising slights; examples of discriminatory mistreatment range from misuse of names and pronouns to outright denial of care for transgender patients (Grant et al, 2011).…”
mentioning
confidence: 99%
“…Finally, ecological perspectives suggest health and health behavior are influenced by factors at individual, community, and policy levels (Sallis & Owen, ). Furthermore, past research has shown that SMY report both financial and privacy barriers to receipt of health care (Snyder et al., ; Williams & Chapman, ). Perhaps the accessible nature of SBHCs helps fill gaps in health care access or reduces access barriers reported by this population.…”
Section: Discussionmentioning
confidence: 99%
“…These multiple levels of influence play important roles in determining barriers, drivers, and supports of individuals’ health behaviors. The accessibility of services in school settings may help reduce SMY's reported privacy (Snyder, Burack, & Petrova, ) and financial (Williams & Chapman, ) barriers to care. Similarly, drawing from social cognitive theory perspectives, SBHCs also may support adolescents’ self‐efficacy to health care and behavior (Bandura, ).…”
mentioning
confidence: 99%
“…Common reported provider-side barriers include provider lack of medical knowledge related to LGBTQ health, unfriendly health system organization, and improper use of pronouns [7,14]. For youth patients, critical barriers include lack of access to gender-affirming care, lack of income or health insurance, lack of cultural competence among healthcare providers, socioeconomic barriers, and discrimination [15].…”
Section: Barriers To Carementioning
confidence: 99%